Comparison of the Physical and Microbiological Characteristics of Peel-off Face Mask Yogurt from Fresh Cow’s Milk and UHT Milk Fermented - Wulan Kartika Sari; Rika Sebtiana Kristantri; Dyan Wigati (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2021)
Yogurt is a product of fermented milk that makes the skin smoother and shinier. Alpha Hydroxy Acid (AHA) in yogurt can increase regeneration and exfoliate skin cells that accumulate on the surface of the stratum corneum. The aims of studied are to compare the physical characteristics and total plate count values ​​of peel-off face mask yogurt made from fresh cow’s milk and UHT milk at 1% and 2% levels. Fresh cow,s milk and UHT milk are heated to 80 ⁰C then cooled to 40-50⁰C. As much as 1% and 2% starter bacteria consisting of Lactobacillus bulgaricus, Streptococcus thermophilus, Lactobacillus acidhophilus, and Bifidobacterium were inoculated into milk then incubated at 37 ⁰C for 7 hours. Yogurt was made into a peel-off mask and evaluated for physical characteristics and total plate number. The result showed that was a statistically significant difference in the physical characteristics of peel-off face mask yogurt made from fresh cow’s milk and UHT milk at 1% and 2% levels.